Pola Komunikasi Jatim Social Care Dinas Sosial Provinsi Jawa Timur Dalam Menangani Permasalahan Sosial - Esa Bagus Wahyu Saputra (CV. ITTC INDONESIA, 2025)
This study aims to analyze the communication patterns applied by Jatim Social Care (JSC) of the East Java Provincial Social Service in addressing various social problems. JSC is a rapid response team formed to address urgent social cases reported by the public, either through social media or other complaint channels. The study employs a descriptive qualitative approach, using data collection techniques such as in-depth interviews, documentation study, and participatory observation. The results indicate that JSC's communication pattern is interpersonal, adaptive, and participatory, utilizing digital communication media such as WhatsApp and social media to enhance coordination and responsiveness. The interpersonal communication strategies used include passive observation, information gathering through third parties, and direct interaction, in accordance with the framework of Berger and Calabrese’s Uncertainty Reduction Theory. These communication patterns not only increase the speed and accuracy of case handling but also strengthen the relationship between volunteers and the community. This research contributes to understanding responsive and collaborative social communication practices in the realm of public service.